Detection and distribution of multi-drug resistant (MDR) bacterial isolates of clinical and public health significance on hospital fomites and hands of healthcare workers in Mubi General Hospital. - Musa Y. Tula * Joel Filgona , Richard Elisha , Terry L. Thomas , Francis O. Iruolaje (Sokoto Journal of Medical Laboratory Science)
Despite the progress made in technology and clinical science, bacterial contamination of hospital fomites, healthcare workers, and the entire environment with its attendant consequences constitute a major problem in many countries of the world. One hundred (100) samples including surfaces of hospital fomites and the hands of healthcare workers were analyzed for bacterial growth on selective and or differential media and the bacteria obtained were identified by standard procedure. The bacterial isolates were screened for antibiotic susceptibility test by the Kirby-Bauer agar disk diffusion method. Of the 100 collected, 77 were from inanimate surfaces while 23 were from the hands of healthcare workers. The predominant inanimate surface swabs collected came from beddings (26%), and the least came from door handles (11.0%). The distribution of samples based on wards showed that 54% of the samples were from female wards, 23% from children's wards, and 20% came from the male ward. Out of 100 samples collected from various sites, bacterial growth was observed in 34(34.0%) specimens while the remaining 66 (66%) had no bacterial growth. A total of 72 bacterial isolates were recovered from the 34 specimens. Overall, Staphylococcus aureus (26.0%) was the most common isolate recovered, while the least was Serratia marcescens and Shigella spp. Of the Gram- negative organisms, Pseudomonas aeruginosa was the most predominant specie, whereas Escherichia coli which represents 50.0% (15/30), predominant Enterobacteriaceae specie encountered. Bacterial isolates were mostly recovered from beddings with 24 isolates, and the least was from sink and door handles with 8 isolates each. Resistance to ampicillin by all the isolates was the highest, but with no statistical difference (P=0.468) with resistance to septrin, and gentamycin. Whereas some isolates were resistant to 9-10 antibiotics, others were resistant to 1-2 antibiotics. From these, the multidrug resistance (MDR) phenotype was shown by 35(66.0%) of these isolates. Escherichia coli portrayed 11(73.3%) MDR phenotypes, while Pseudomonas aeruginosa exhibited 8(50.0%) MDR phenotypes. Multiple antibiotic resistance (MAR) index of greater than 0.2 was shown by 38(71.7%) bacterial isolates. Of these, 12(31.6%) and 9(23.7%) were from E. coli and P. aeruginosa respectively. Most of the bacterial isolates that were resistant to at least an antibiotic were commonly isolated from patients' beddings (30.2%), tables (28.3%), and sinks (20.8%). This study, therefore, shows that hands of healthcare workers and inanimate surfaces frequently touched within the hospital environment constitute potential reservoirs for emerging MDR pathogens and may also serve as sources of their transmission.